Analysis on Dynamics of Delayed Intraguild Predation Model with Ratio-Dependent Functional Response - Magudeeswaran, S.; Sathiyanathan, K.; Sivasamy, R.; Vinoth, S.; Sivabalan, M. (Discontinuity, Nonlinearity, and Complexity, 2026)
The aim of this work is to analyze the dynamics of intraguild predation model with ratio-dependent functional response and time-delay. We examine the conditions for local stability and existence of Hopf-bifurcation. Also, the condition for global stability is established by using proper Lyapanov function. Finally numerical simulations are given to verify the proposed theoretical results and the system investigate through graphical illustrations.